ABOUT THE RESULTS OF TESTS CONDUCTED ON VI GRADE STUDENTS IN THE GREATER STIP AREA (Philological Studies, 2019)
Morphological features of the parts of speech, more precisely nouns, adjectives, verbs, pronouns and numbers, are part of the curriculum for VI grade, given by the Bureau for Development of the Education. The target group of the research will be grade VI students in the Greater Shtip area. Given that the mentioned parts of speech are first adopted in the sixth grade, the testing will be conducted on these students. In this respect, we will prepare an integral test in Macedonian language (mother tongue) that contains tasks in which morphological features will be tested. The tasks will be fully or partially taken from the current textbooks in Macedonian language (mother tongue), but also from other sources of scientific and professional literature in Macedonian language. Prior to the test, through an anonymous survey we will determine the number of students that will take the test. The purpose of this paper is to analyset he results given by the grade VI students in Greater Shtip area, to see how much they have learned the morphological features of the parts of speech and to see if they made any language errors.
Keywords: morphology, modal words, VI grade students, tests, exercises